2016
DOI: 10.1007/s10585-016-9780-3
|View full text |Cite
|
Sign up to set email alerts
|

β-catenin-independent WNT signaling and Ki67 in contrast to the estrogen receptor status are prognostic and associated with poor prognosis in breast cancer liver metastases

Abstract: Liver metastasis development in breast cancer patients is common and confers a poor prognosis. So far, the prognostic significance of surgical resection and clinical relevance of biomarker analysis in metastatic tissue have barely been investigated. We previously demonstrated an impact of WNT signaling in breast cancer brain metastasis. This study aimed to investigate the value of established prognostic markers and WNT signaling components in liver metastases. Overall N = 34 breast cancer liver metastases (wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 58 publications
4
40
0
2
Order By: Relevance
“…A variety of different cancers have been found to express ROR1. 23 To date, high-level expression of ROR1 has been found to have adverse prognostic significance for patients with breast cancer, [24][25][26][27] ovarian cancer, 28,29 melanoma, 30 or Ewing sarcoma. 31 Moreover, high-level expression of ROR1 also has been associated with higher levels of AKT activation, 24,30,32,33 consistent with the notion that ROR1 signaling leading to activation of AKT may serve as a driver, not just in CLL, but also in other malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of different cancers have been found to express ROR1. 23 To date, high-level expression of ROR1 has been found to have adverse prognostic significance for patients with breast cancer, [24][25][26][27] ovarian cancer, 28,29 melanoma, 30 or Ewing sarcoma. 31 Moreover, high-level expression of ROR1 also has been associated with higher levels of AKT activation, 24,30,32,33 consistent with the notion that ROR1 signaling leading to activation of AKT may serve as a driver, not just in CLL, but also in other malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…23 As we all know, Ki67 is a good marker of cell proliferation in a variety of tumors and lymph node metastasis indicates high invasion and migration of tumors, which can be used for prognostic assessments of patients with cancer. [24][25][26][27][28][29] Further prognostic analysis of the Kmplot online database conrmed this point which showed that the breast cancer patients with low PHF2 expression frequently have shorter OS and RFS compared to the high expression group. In further studies, we will assess the prognosis of different histological types of breast cancer with a large sample and a longer followup period.…”
Section: Discussionmentioning
confidence: 82%
“…This way they are not favorable to form the Top1‐DNA cleavage complex. Second, breast cancer cells are reported to utilize aberrant Wnt signaling to overcome apoptosis . Owing to epigenetic activation of Wnt signaling, DEHP‐exposed MCF‐7 cells might escape from the cytotoxic effects of CPT.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple oncogenic signaling pathways that contribute to estrogen‐induced therapeutic failures, including the activation of PI3K/Akt, Wnt/β‐catenin, NF‐κB, MAPK/ERK pathways and a set of receptors such as human epidermal growth factor receptor‐2 (HER2), epidermal growth factor receptor (EGFR), fibroblast growth factor receptor (FGFR) and insulin‐like growth factor 1 receptor (IGF1R) . However, it is difficult to rule out the possibility that the acquired drug resistance in cancer is triggered by epigenetic regulation.…”
Section: Introductionmentioning
confidence: 99%